Corporate Restructuring and Its Macro Effects - Shin, Jongsoon (Washington, D.C. : International Monetary Fund, 2017)
This paper describes issues in Korea's corporate sector, the need for restructuring, and the authorities' initiatives and challenges. It then identifies lessons from other countries' experience and conducts an econometric analysis based on cross-country aggregate data, compared with previous studies which mostly use firm-level data. This analysis finds that restructuring episodes, while sometimes challenging in the short term, have typically been associated with more rapid economic growth afterward. Corporate restructuring could have a negative effect on the labor and the financial markets in the short term, but is associated with positive growth through increased investment and capital productivity in the medium term, outpacing the negative effects.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet